PENGARUH MODEL DISCOVERY TERHADAP HASIL BELAJAR IPA DI SD - Yunita, Amalia; Kresnadi, Hery; Margiyati, KY (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the effect of discovery models on the results of learning Natural Sciences class V students of Elementary School 05 East Pontianak. The research method used was an experiment with a quasi experimental design, with the experimental design of nonequivalent control group design. The sample was determined by purposive sampling technique or consideration so that the VA class sample was 27 students as the experimental class and VB was 27 students as the control class. The source of this research data is the test answer sheet for fifth grade students of Sekolah Dasar Negeri 05 Pontianak Timur. Data collection techniques use measurement techniques. The instrument used is a test of student learning outcomes. Based on the calculation obtained the average learning outcomes of post-test control class 71.61 and the average learning outcomes of experimental class 75.72 so that the post-test data t_count is 2.18924 with t_tabel for the significant level Î± = 5% and dk 52 is 1,9664 because t_count (2,18924)> t table (1,9664) then Ha is accepted. So, there is a significant influence on the use of discovery models on the learning outcomes of Natural Sciences in fifth grade students of East Pontianak Public Elementary School 05. From the effect size (ES) calculation, it is obtained 0.42 (medium criteria). This means that the use of discovery models gives a moderate influence on the results of learning Natural Sciences students of class V Students of Elementary School 05 East Pontianak.Â Key words : influences, discovery, learning outcomes, natural Â science.